Integrated Port Time Control for Shipping Companies - Asyqar Prabowo Aji; Paulus Raga; Yosi Pahala; Prasadja Ricardianto; Zaenal Abidin (Institut Transportasi dan Logistik Trisakti, 2022)
As the busiest port in Indonesia, Tanjung Priok port has a hard time to achieve the target to maximize ship utility through operational cost savings. The purpose of this study is to determine the factors affecting Integrated Port Time (IPT) in order to reduce the shipping companies operating costs in Tanjung Priok Port, Jakarta. Controllable and uncontrollable IPT is influenced by five variables which are the availability of the docks, the shipping lane conditions, the document services, the guidance services, and the loading-unloading productivity. This study focuses on the factors that affect IPT in domestic area of Terminal 3 Tanjung Priok Port Jakarta in particular. It is related to how IPT could contribute to the efficiency of national companies operations in general if the duration is shortened. This study used Path Analysis method with a total sample of 70 people from the operational team and the crew of Temas shipping company. The results of the study prove that five variables mentioned have a positive and significant impact altogether on IPT of the ships operated by Temas shipping company in Tanjung Priok port in Jakarta. The findings are expected to be useful to cut down Temas shipping company’s operational cost and increase the ships utility.